Subcritical Water Extraction of Fucoidan from Sargassum polycystum: A Sustainable Approach - Pavithra, P. A.; Mohanan, Vidya; Kumar, Lekshmi R. G.; Anas, K. K.; Anandan, R. (Fishery Technology, 2026)
Subcritical water extraction (SWE) is receiving increasing attraction as an emerging green technique for the extraction of bioactive compounds from diverse sources. The present study has been carried out to investigate the potential of SWE for extraction of fucoidan from Sargassum polycystum. The extraction was carried out under optimal conditions of extraction temperature (180 °C), pressure (40 bar), and a solid-to-liquid ratio of 1:20 for 60 min. The SWE process yielded 5.24% fucoidan, demonstrating the effectiveness of SWE in extracting bioactive compounds from brown seaweed. The SWE extracts exhibited fucose and sulfate contents of 21.36% and 26.9%, respectively, which are consistent with the typical composition of fucoidan derived from brown seaweeds. The uronic acid content was determined to be 3.39%. Overall, this study highlights the potential of SWE as a green alternative for fucoidan extraction, capable of preserving polysaccharide bioactivity while reducing environmental impact.